An Exploratory Study on the Interaction Between Fear of Missing Out (FoMO) and Rumination in Increasing Social Anxiety and Excessive Social Media Use Among University Students - Kareem, Mohammad Al-Safi Abdul; Al-Munif, Najood Mohammed Abdulaziz (Journal of Ecohumanism, 2024)
The study aimed to explore the impact of the interaction between Fear of Missing Out (FoMO) and rumination on increasing the levels of social anxiety and excessive use of social media among university students. The study was conducted on a sample of 423 university students, utilizing the following scales: FoMO scale, developed by Przybylski et al. (2013) translated and adapted by Professor Dr. Mohammad Al-Safi (2024). Social Anxiety Scale by Liebowitz, translated and adapted by Professor Dr. Ibrahim El-Shafie (2015). Ruminative Thought Styles Questionnaire (RTSQ) by Brinker & Dozois (2009) translated and adapted by Professor Dr. Ibrahim El-Shafie (2015). The study found the following results: There is a statistically significant positive correlation between Fear of Missing Out (FoMO) and social anxiety, with a correlation coefficient of (0.635), significant at the 0.01 level. There is a statistically significant positive correlation between Fear of Missing Out (FoMO) and excessive use of social media, with a correlation coefficient of (0.730), significant at the 0.01 level. There is a statistically significant positive correlation between rumination and social anxiety, with a correlation coefficient of (0.567), significant at the 0.01 level. There is a statistically significant positive correlation between rumination and excessive use of social media, with a correlation coefficient of (0.824), significant at the 0.01 level. There is a significant interaction between FoMO and rumination on social anxiety, with the F-values indicating that the interaction has a significant effect at the 0.01 level. The model highlights that FoMO and rumination are key psychological factors that, when interacting, contribute to the overuse of social media platforms among individuals. This interaction indicates that those experiencing higher levels of both FoMO and rumination are more likely to engage in excessive social media usage, which is statistically significant at the 0.01 level.